Calibration of Atom Probe Tomography Reconstructions Through Correlation with Electron Micrographs. (4th February 2019) - Mouton, Isabelle; Katnagallu, Shyam; Makineni, Surendra Kumar; Cojocaru-Mirédin, Oana; Schwarz, Torsten; Stephenson, Leigh Thomas; Raabe, Dierk; Gault, Baptiste
Abstract: Although atom probe tomography (APT) reconstructions do not directly influence the local elemental analysis, any structural inferences from APT volumes demand a reliable reconstruction of the point cloud. Accurate estimation of the reconstruction parameters is crucial to obtain reliable spatial scaling. In the current work, a new automated approach of calibrating atom probe reconstructions is developed using only one correlative projection electron microscopy (EM) image. We employed an algorithm that implements a 2D cross-correlation of microstructural features observed in both the APT reconstructions and the corresponding EM image. We apply this protocol to calibrate reconstructions in a Cu(In, Ga)Se2 -based semiconductor and in a Co-based superalloy. This work enables us to couple chemical precision to structural information with relative ease.